PRAGMATIC TRANSFER IN APOLOGY EMPLOYED BY ENGLISH EDUCATION STUDENTS OF ISLAMIC STATE UNIVERSITY (UIN) RADEN FATAH - Tiara Eliza (University of Kuningan, 2019)
This study intends to find out and to describe apology strategies made by the sixth and eighth semester students of English Education Study Program of Islamic State University (UIN) Raden Fatah Palembang, and to explain how the pragmatic transfer interferes the apology strategies. This study used a qualitative descriptive design. Written discourse completion tasks and observation by doing a role play were used as the instruments to obtain the data. There were 66 students selected as the subjects of study. The data obtained were analyzed based on the classification of apology strategy proposed by Olshtain and Cohen (1983). As result, it was found that there were five apology strategies made by the students, for example, using the word sorry to express regret was considered the most frequently used strategy. Then, the result also showed that the speakers who have low social status tend to use polite strategy in all levels of social relationships (strangers and acquaintances). For the speakers who have high social status and equal tend to use less polite and casual expressions, respectively. Moreover, some students use some pragmatic transfers in expressing apology strategies influenced by their L1 (mother tongue) or L2 (Indonesian) culture.